Twitter como herramienta para fomentar la participación ciudadana. El caso de los gobiernos de España y Cuba - Sánchez Ramos, Aida (2021)
This article explores and documents the incidence of the use of Twitter in the call for citizen participation by the main institutions and governmental figures of Cuba and Spain, in a period covering the daily life before the COVID-19 pandemic and the first months in which the disease hit the life of both countries. A quantitative methodology is used for the analysis, which will allow to compare the behavior of both governments, in terms of modernization of public authorities and the incentive for the population to get involved in the communication strategies established in social networks. The results indicate that we are in the presence of two digital communicative alternatives that, although numerically they do not seem to be far apart, differ in terms of the purpose of the calls to action and in the way of linking the resources of the microblogging network to determine the reaction of the citizens to whom they summon. This research delves into case studies to provide a broader perspective on government behavior towards citizens in different political contexts.